Effect of Traditional Chinese Formula Dingkun Pill on Primary Dysmenorrhea: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial - Xuesong Ding; Shiyang Zhu; Yan Deng; Xiao Ma; Jingwen Gan; Yanfang Wang; Aijun Sun (Clinical and Experimental Obstetrics & Gynecology)
Background: Primary dysmenorrhea (PD) afflicts many childbearing-age women, with a high prevalence ranging from 17% to 90%. The Dingkun pill (DKP), a traditional Chinese medicine formula, has been prescribed for managing menstrual disorders empirically in clinical practice for a long time, but there are very few high-quality studies supporting this practice. Therefore, this trial aimed to assess the efficacy and safety of DKP in patients with PD. Methods: Our study was a multicenter, prospective, randomized, double-blind, placebo-controlled study. DKP or placebo was prescribed to participants from the 5th to 14th day of each menstrual cycle for 12 weeks. Changes in pain intensity were measured by a visual analog scale (VAS) and were compared between groups using repeated measures analysis. The pain mediators and sex hormones were also assessed before and after the treatment, and their intergroup changes from the baseline were analysed by student t-test. The hemodynamic indices and safety profile of DKP were also investigated. Results: A total of 156 women were recruited and randomly allocated to receive either DKP or placebo, of whom 142 (73 in DKP and 69 in sham control) completed the study. A more distinctive reduction in VAS scores was observed in the DKP group, compared with placebo (–2.68 ± 0.21 vs. –1.29 ± 0.14, p < 0.001). Compared to placebo, DKP treatment resulted in a pronounced suppression of serum PGF2α, oxytocin and vasopressin, along with a significant increase in beta-endorphin level (p < 0.001). Moreover, uterine artery flow measured by ultrasonography indicated increased blood perfusion after DKP treatment (p < 0.01), while no change was detected in the placebo group. Additionally, except for an inhibited serum follicular stimulating hormone (FSH) (p = 0.037), no statistical difference in hormonal status and safety indicators was detected before and after the treatment. Conclusions: DKP treatment attenuated pain severity in patients with primary dysmenorrhea, and no harmful side effect was observed during 12 weeks of treatment. Clinical Trial Registration: ClinicalTrials.gov, NCT03953716. Registered 17 May 2019. https://clinicaltrials.gov/ct2/show/NCT03953716.